Impact of Chemotherapy Treatments on Dietary Intakes of Macro and Micronutrients among Jordanian Women with Breast Cancer - Safaa A. Al-Zeidaneen; MousaA.Ahmad; Ali D. Al-Ebuos (Journal of Pharmacy and Nutrition Sciences, 2018)
Background: Breast cancer (BC) is the leading cause of cancer related deaths among women worldwide. Nutritional factors may account for the large variation in BC incidence around the world. Most studies have shown no link between dietary intakes and increased risk of BC. Objective: To evaluate the dietary intake of macro and some micronutrients among BC patients with respect to chemotherapy treatment. Methods: A total of 168 BC patients aged 20-70 years attending BC clinics at the Jordanian Royal Medical Services, Jordan were evaluated for dietary intake. The study design permitted to include 60 newly-diagnosed BC patients who were not exposed to any type of interventions and 108 recently-diagnosed BC patients (up to three months). Recently group member were sub-divided in two sub-groups to control exposure to chemotherapy. The Chemo group (have exposed to chemotherapy) and the non-chemo group (have exposed to other types of treatments interventions). Calculations were based on the computerized nutrient analysis program (the food processor nutrition and fitness analysis software (ESHA), version 10.6/.3, Salem, USA). Results: Energy, macronutrients and micronutrients intakes were not significantly different considering exposure to chemotherapy. However, they were less than recommended in all BC patients. Conclusion: The possible risk of dietary undernutrition among BC patients that need a careful monitoring, evaluation and managements care plan.